Language learning, discourse and cognition studies in the tradition of Andrea Tyler - Pickering, Lucy, 1966-; Evans, Vyvyan (Human cognitive processing (HCP) cognitive foundations of language structure and use,, 2018)
"Language Learning, Discourse and Cognition: Studies in the tradition of Andrea Tyler comprises a collection of original empirically and theoretically motivated studies at the nexus of discourse analysis, cognitive linguistics and second language learning. The thematic relationships between these subfields and links between the studies are laid out in introductory and concluding chapters. This edited volume is intended for both researchers and taught graduates in linguistics and second language learning and teaching"--